2020
DOI: 10.1111/odi.13175
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the oral microbiome and oral health among patients receiving clear aligner orthodontic treatment

Abstract: Objectives This 6‐month prospective clinical study assessed the impacts of Invisalign appliances on the oral bacterial community and oral health of patients. Methods Salivary samples were obtained from twenty‐five adult patients receiving Invisalign aligner treatment before the treatment (Group B) and at a 6‐month follow‐up (Group P). The bacterial composition of each sample was determined using Illumina MiSeq sequencing of the bacterial 16S rRNA. Intra‐ and intergroup biodiversity was analyzed. Clinical perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 38 publications
1
32
1
1
Order By: Relevance
“…The results of the study and our study including saliva sample strongly suggested the increase of the genus Tannerella in oral cavity after placement of orthodontic appliances. Zhao et al reported that there were significant decrease of Prevotella abundance and overall microbial community structure did not change in saliva in spite of using NGS method as our study 44 . It is speculated that their contrast result to our finding of increased periodontal pathogens were due to the different types of orthodontic appliances; whereas we targeted fixed orthodontic appliances, they targeted removal orthodontic appliances.…”
Section: Discussionmentioning
confidence: 49%
“…The results of the study and our study including saliva sample strongly suggested the increase of the genus Tannerella in oral cavity after placement of orthodontic appliances. Zhao et al reported that there were significant decrease of Prevotella abundance and overall microbial community structure did not change in saliva in spite of using NGS method as our study 44 . It is speculated that their contrast result to our finding of increased periodontal pathogens were due to the different types of orthodontic appliances; whereas we targeted fixed orthodontic appliances, they targeted removal orthodontic appliances.…”
Section: Discussionmentioning
confidence: 49%
“…Among Rothia genus, the lower abundance was shown in group C rather than in both groups CAT and FAT, although a significant difference ( P < 0.05) was shown only between C and FAT groups, which showed the higher abundance. Zhao et al [ 36 ] analyzed 6-month effects of CAT on salivary bacterial community. No significant changes in biodiversity (alpha and beta diversity) were detected in time.…”
Section: Resultsmentioning
confidence: 99%
“…The main advantage of clear aligner therapy over conventional multibracket orthodontics is the lack of bonded components. It is well known that fixed orthodontic appliances can alter oral microbiome [31], whereas clear aligner therapy has minimal effects on the mouth environment [32]. However, the exact effect of clear aligners in the oral cavity has still to be investigated.…”
Section: Discussionmentioning
confidence: 99%